An appraisal of the BRACs NFPE Programme in respect to coverage of terminal competencies specified by the government of Bangladesh - Ghosh, Sanat K. (BRAC Research and Evaluation Division (RED), 2020)
The study aimed to make an appraisal of the three-year Non-Formal Primary Education (NFPE) programme of BRAC in respect to the terminal competencies identified by the government of Bangladesh for the Formal Primary Education (FPE) cycle. The two-way content analysis was conducted in respect to three sources of materials - (i) Text Materials (TM), (ii) Curriculum Transaction Materials (CTM) and (iii) Evaluation Materials (EM) by three types of competencies - (i) Psycho-motor, (ii) Cognitive and (iii) Affective. The coverage was qualified in terms of well covered (WC) , trurly covered (FC) , or not covered (NC). Subject-based learning objectives ( continua) were also compared between the three-year NFPE and the FPE cycle up to third grade. Findings indicated that on an average, the three-year NFPE programme was covering fairly well in respect to the TM and CTM sources. But there is a scope to improve the evaluation materials. In respect to the subject-based learning objectives only five objectives were not covered but at the same time it was covering about 60 additional leaning objectives . The whole NFPE programme was found unique in its character particularly in terms of material development and curriculum transaction.